2018
DOI: 10.30609/jeti.2018-1.5303
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection of 1020 steel by conducting films electrodeposited in methanesulfonic acid

Abstract: 1020 steel is widely used in the industrial sector, however it is a reactive metal and susceptible to corrosion, being necessary to use surface coatings to protect the metal in corrosive media. The polyaniline and polypyrrole are conducting polymers that have the ability to inhibit corrosion when deposited in organic media. In this work, corrosion protection was investigated through polyaniline and polypyrrole films electrodeposited in methanesulfonic acid medium. The films were electrodeposited by chronoamper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Estudos eletroquímicos prévios mostraram que o filme de PPy é depositado no eletrodo de aço através de ensaios de voltametria cíclica. Foi observado que as correntes anódicas começaram a aumentar a partir de +1,0 V vs Ag/AgCl, indicando a oxidação do monômero e deposição do filme polimérico 12 .…”
Section: Resultado E Discussãounclassified
“…Estudos eletroquímicos prévios mostraram que o filme de PPy é depositado no eletrodo de aço através de ensaios de voltametria cíclica. Foi observado que as correntes anódicas começaram a aumentar a partir de +1,0 V vs Ag/AgCl, indicando a oxidação do monômero e deposição do filme polimérico 12 .…”
Section: Resultado E Discussãounclassified
“…(Eslami et al, 2019) Regarding the state of the art of the theme addressed in this study, it is observed that references on "Chemical and electrochemical deposition of polypyrrol on lead alloy surface" are scarce (Eftekhari & Ahmadi, 2006). Regarding deposition on metallic substrates such as magnesium, copper, aluminum, zinc, stainless steel, there is a good database previously published (Menkuer & Ozkazank, 2019;Vera et al, 2014;Sheng et al, 2014;Mortazavi et al, 2019;Samad et al, 2019;Sharifirad et al, 2010;Annibaldi, Rooney, & Breslin, 2012;Ferreira, Liu, & Cho, 2018;Souza, Liu, & Cho, 2018;Liu, Bezerra, & Cho, 2017).…”
Section: Introductionmentioning
confidence: 91%